Orientational ordering of Janus colloids in cholesteric liquid crystals1. Issue 37 (7th October 2015) - Rudyak, Vladimir Yu.; Emelyanenko, Alexander V.
<x xml:space="preserve">Abstract</x> In this paper we show that Janus colloids, which are spherical particles with hybrid anchoring conditions, have preferable orientations in cholesteric media depending on the cholesteric wave vector.